Malaysia National Education Blueprint: An Overview on the Policy of Recruitment and Selection of Teachers - Syed MuhamadUbaidillah, Syed Husin
The purpose of this study was to explore the policy of recruitment and selection of teachers and their impacts on organizational performance.It was to find out the impacts and the challenges associated with the poor teacher recruitment and selection practice and ways to help improve human resource planning and development. High turnover, teacher quality, retraining of teacher and organization’s goals were amongst the issues. Special reference was given to the latest Malaysia’s educational policy - Malaysia National Education Blueprint (2013-2025) (MNEB). The study tries to answer three questions namely; Why the Blueprint has included human resource management (HRM) in its transformation program as one of the key initiatives?How far is the influence of Teachers’ Unions in the making of Human Resource policy in education and to what extent the existing recruitment and selection policy has given impacts to the country’s educational system?.